2007
DOI: 10.1080/00016340701647341
|View full text |Cite
|
Sign up to set email alerts
|

Leisure time physical activity during pregnancy and impact on gestational diabetes mellitus, pre‐eclampsia, preterm delivery and birth weight: a review

Abstract: Thus, it seems relevant that health authorities recommend 30 min of daily physical activity to healthy pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
95
2
14

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(118 citation statements)
references
References 65 publications
7
95
2
14
Order By: Relevance
“…In contrast, however, a series of recent reports have linked pre-gravid physical activity with a reduced risk of GDM (6,(13)(14)(15)(16)(17). Although these reports have established this important association, it should be noted that neither the types of exercise nor the physiologic mechanisms underlying this protective effect have been well studied.…”
Section: Introductionmentioning
confidence: 64%
“…In contrast, however, a series of recent reports have linked pre-gravid physical activity with a reduced risk of GDM (6,(13)(14)(15)(16)(17). Although these reports have established this important association, it should be noted that neither the types of exercise nor the physiologic mechanisms underlying this protective effect have been well studied.…”
Section: Introductionmentioning
confidence: 64%
“…In a metaanalysis of 11 clinical studies Choi et al described significant effects of exercise and nutrition on gestation-associated weight gain in overweight and obese pregnant women [12]. The prevalence of gestational diabetes in particular is higher among physically inactive and overweight women, and this is associated with increased perinatal morbidity and mortality and birth-related complications [2,13,14]. Excessive weight gain in obese pregnant women also increases the risk of premature birth [15].…”
Section: Introductionmentioning
confidence: 99%
“…Although shifting the occurrence of a large for gestational age baby to a normal range has benefits for maternal outcomes, elevated birth weight is not always observed and therefore cannot always be assumed in human studies or animal models of maternal over-nutrition. Indeed, birth weight data in the above mentioned studies [24][25][26][27] and our recent review of maternal high-fat feeding and offspring development show birth weight is often similar between offspring groups or in fact lower in offspring of obese mothers compared with controls. 28 A major limitation of human studies is the degree to which a mechanistic understanding may be achieved without invasive procedures in children.…”
Section: Maternal Obesity And/over-nutrition Predisposes Offspring Tomentioning
confidence: 99%
“…Increasing attention towards interventions that may be used to improve maternal health could, therefore, impact substantially on offspring health both in the short and long term. A number of early reviews, 19,[22][23][24][25] in addition to two recent studies, 26,27 have identified altering maternal carbohydrate intake as well as maternal physical activity levels as potential strategies for positively regulating maternal weight gain and offspring birth weight among other pregnancy outcomes. However, longitudinal studies that describe the potential long-term benefits of these interventions for offspring health are lacking.…”
Section: Maternal Obesity And/over-nutrition Predisposes Offspring Tomentioning
confidence: 99%